Implementasi Peraturan Daerah Nomor 2 Tahun 2015 Dalam Penataan Pedagang Kaki Lima Di Kota Denpasar - Cokorda Istri Sinta Sukma Ratih; Anak Agung Gede Oka Wisnumurti; Made Detrichyeni Winaya (Public Inspiration : Jurnal Administrasi Publik, 2018)
This study, aims to determine the implementation of Regional Regulation No. 2 of 2015 in the arrangement of street vendors in Denpasar City, which includes the process of socialization of local regulations, implementation, up to the enforcement carried out by Satpol PP Denpasar City as law enforcement and to determine the factors that influence the implementation of street vendors in Denpasar City, both in the form of supporting factors and inhibiting the implementation process. To answer this problem, a qualitative descriptive research method was used. Data analysis was carried out using Merilee S. Grindle's policy implementation theory and contingency theory developed by James Lester. The results showed that the Implementation of Regional Regulation No. 2 of 2015 in the Arrangement of Street Vendors (PKL) in Denpasar City could be divided into street vendors organized by banjars or traditional villages and independent organized PKL. The street vendor arrangement has not run optimally so far, this is because there are still many street vendors who have been netted and the number of street vendors continues to increase every year. The Merilee S. Grindle theory is used as a measurement tool for policy implementation, using two variables: the degree of change desired and the aspects of the power, interests, and strategies of the actors involved. In practice, the arrangement of street vendors is still faced with several obstacles, especially in terms of implementation and precisely the village or customary village that plays an important role in managing street vendors in its working area. Whereas the supporting factor comes from the aspect of local regulation socialization. In contingency theory shows that the implementation of the law in the arrangement of street vendors in the city of Denpasar is still stuggler.